Social logistics: Rethinking public transport as a regional distributor of goods in rural areas. Chances for the long-term establishment of a sustainable regional logistics approach; Soziale Logistik: Öffentlicher Nahverkehr als regionaler Verteiler von Gütern in ländlichen Regionen. Chancen für die langfristige Etablierung eines nachhaltigen regionalen Logistikkonzepts - Eva Greischel; Emilia Nagy; Alexander Conrad; Martina Schäfer (Raumforschung und Raumordnung / Spatial Research and Planning, 2024)
This paper presents initial findings on the establishment of a social logistics project in a peripheral rural region in Germany. As part of a real-life laboratory, two services were developed and tested with the aim of improving rural supply: the delivery of regional goods and the return of online orders in cooperation with a regional public transport provider, regional retailers and parcel services. An evaluation team provided support to the project in identifying, monitoring, and documenting the societal impact of the services and promoted impact-oriented project management. The concept of providing services of general interest through social logistics and testing them in a real-world laboratory was based on preliminary work in the region. The results indicate that this approach can promote this type of social logistics in the long term. A social logistics approach does not focus solely on economic aspects but emphasises social and environmental benefits for the region. A real-world laboratory approach enables an environment that promotes open exchange, involvement of different stakeholders and joint problem solving in a reflective, iterative process. This methodological approach enabled the continuation and out-scaling of the service's core offerings immediately after ending the test phase and is seen as an important prerequisite for establishing a long-term perspective. – – In diesem Beitrag werden erste Erkenntnisse zur Etablierungvon Soziallogistik in einer peripheren ländlichen Region in Deutschland vorgestellt. Im Rahmen eines Reallabors wurden zwei Dienstleistungen mit dem Ziel der Verbesserung der Versorgung des ländlichen Raums zwei Dienstleistungen entwickelt und erprobt: die Zustellung regionaler Waren und derRückversand von Online-Bestellungen in Zusammenarbeit mit einem regionalen ÖPNV-Anbieter, regionalen Händlern und Paketdiensten. Ein Evaluationsteam unterstützte das Projektbei der Identifizierung, dem Monitoring und der Dokumentation der gesellschaftlichen Wirkungen der Dienstleistungenund förderte eine wirkungsorientierte Projektsteuerung. Der Ansatz der Etablierung von Dienstleistungen der Daseinsvorsorge in Form sozialer Logistik und die Erprobung im Rahmeneines Reallabors erschienen auf der Basis von Vorarbeiten inder Region sinnvoll. Die bisherigen Ergebnisse weisen daraufhin, dass diesesVorgehen Potenzial hat, die Langfristperspektive für den entwickelten Logistikansatz zu fördern: SozialeLogistik stellt nicht allein auf ökonomische Aspekte ab, sondern betont den sozialen und ökologischen Mehrwert für die Region. Ein Reallaboransatz ermöglicht ein Umfeld, das denoffenen Austausch, die Einbeziehung verschiedener Interes-sengruppen und die gemeinsame Problemlösung in einemreflexiven und iterativen Prozess fördert. Dieses methodischeVorgehen ermöglicht darüber hinaus eine Weiterführung und Ausbreitung der Kernangeboteder Dienstleitung unmittelbarnach der Testphase und wird als wichtige Voraussetzung fürdie langfristige Perspektive angesehen.
Keywords: 710; Real-World Laboratory; Regional Economics; Rural Areas; Social Innovations; Social Logistics; Soziale Logistik; Ländliche Räume; Regionalökonomie; Soziale Innovationen; Reallabor